PEG–PLGA nanoparticles for encapsulating ciprofloxacin - Natsorn Watcharadulyarat; Monthira Rattanatayarom; Nisarat Ruangsawasdi; Nisa Patikarnmonthon (2023)
Antibiotic medications have been found to hinder the success of regenerative endodontic treatment due to the rapid degradation of the drug, and the acidic nature of ciprofloxacin (CIP) can be harmful to stem cells of the apical papilla (SCAPs), the cells responsible for regeneration. In this study, a nanocarrier system was used for controlled drug release for longer drug activity and less cytotoxicity to the cells. CIP was loaded in poly (ethylene glycol) methyl ether-block-poly (lactide-co-glycolide) (PEG-PLGA) nanoparticles (NPs) with an ion-pairing agent. The NPs demonstrated a monodispersed spherical morphology with a mean diameter of 120.7 ± 0.43 nm. The encapsulation efficiency of the CIP-loaded PEG-PLGA NPs was 63.26 ± 9.24%, and the loading content was 7.75 ± 1.13%. Sustained CIP release was achieved over 168 h and confirmed with theoretical kinetic models. Enhanced NP bactericidal activity was observed against Enterococcus faecalis. Additionally, CIP-loaded PEG-PLGA NPs had a low cytotoxic effect on SCAPs. These results suggest the use of a nanocarrier system to prolong the antibiotic activity, provide a sterile environment, and prevent reinfection by the bacteria remaining in the root canal during regenerative endodontic treatment.